FAM96A Protects Mice From Dextran Sulfate Sodium (DSS)-Induced Colitis by Preventing Microbial Dysbiosis - Ang Yin (Frontiers in Cellular and Infection Microbiology, 2019)
Family with sequence similarity 96 member A (FAM96A) is an evolutionarily conserved intracellular protein that is involved in the maturation of the Fe/S protein, iron regulatory protein 1 (IRP1), and the mitochondria-related apoptosis of gastrointestinal stromal tumor cells. In this study, we used a mouse model of chemically induced colitis to investigate the physiological role of FAM96A in intestinal homeostasis and inflammation. At baseline, colons from Fam96a−/− mice exhibited microbial dysbiosis, dysregulated epithelial cell turnover, an increased number of goblet cells, and disordered tight junctions with functional deficits affecting intestinal permeability. After cohousing, the differences between wild-type and Fam96a−/− colons were abrogated, suggesting that FAM96A affects colonic epithelial cells in a microbiota-dependent manner. Fam96a deficiency in mice resulted in increased susceptibility to dextran sulfate sodium (DSS)-induced colitis. Importantly, the colitogenic activity of Fam96a−/− intestinal microbiota was transferable to wild-type littermate mice via fecal microbial transplantation (FMT), leading to exacerbation of DSS-induced colitis. Taken together, our data indicate that FAM96A helps to maintain colonic homeostasis and protect against DSS-induced colitis by preventing gut microbial dysbiosis. This study used gene knockout animals to help to understand the in vivo effects of the Fam96a gene for the first time and provides new evidence regarding host–microbiota interactions.